MOLECULAR IDENTIFICATION OF DENITRIFYING BACTERIA TO EVALUATE THE SENSITIVITY OF SELECTIVE MEDIA - Dianti Eka Yurnaningsih; Niniek Widyorini; Aninditia Sabdaningsih (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2021)
Eutrophication is the main problem in Rawa Pening that occurs due to the high supply of organic material from various sources. The high level of nitrate in the water can be reduced through denitrification mechanism using some bacteria such as Pseudomonas group. This bacteria group was often isolated using Glutamate Starch Phenol (GSP) selective media. This study aims to identify the species from the floating net cage of Rawa Pening that was suspected as Pseudomonas group based on colony morphology in GSP through molecular approach, build the phylogenetic tree, and analyze the genetic distance. The research was conducted from January to May 2020. The molecular approach was carried out using the Polymerase Chain Reaction (PCR) method with 16S rRNA gene amplification. The results of BLAST analysis showed that isolate D1 which obtained from water samples in the Rawa Pening floating net cage area had 99.23% homology with Acinetobacter junii strain tu13. The partial sequence of DNA was already deposited to GenBank with accession number LC603787. The phylogenetic tree construction was built using Neighbor-Joining analysis on MEGA X software. The results showed that isolate D1 was related to Acinetobacter junii strain tu13 with 0.006 genetic distance while Pseudomonas fluorescens with 0.144 genetic distance. The result revealed that isolate D1 closely related to A. junii rather than Pseudomonas group. This study indicated that GSP medium has a sensitivity range at the Order level, namely Pseudomonadales.